دور الابتكار التسويقي في تحقيق ميزة تنافسية للمؤسسة الاقتصادية الجزائرية دراسة حالة مؤسسة صناعة الكوابل - فرع جنرال كابل – بسكرة - قريشي, د/ محمد (Sciences humaines; Vol. 42 (2015): SCIENCES HUMAINES (Novembre ), 2016)
This study aimed to identify the role played by marketing innovation of various dimensions (product innovation, promoting innovation,  distributional innovation,  price innovation) in achieving a competitive advantage for national economic institutions and to focus on the case of Cable Industry Foundation.        To achieve the objectives of the study, we have designed and distributed a questionnaire on the study population, and to analyze the data, we relied on SPSS program. V19, where the use of descriptive statistical methods to determine the respondents' perceptions for the level of  marketing innovation, and the level of achieving the competitive advantage in the studied institution. For testing the hypotheses of the study the multiple regression analysis has been used (Multiple Regression Analysis), and analysis of variance of the slope (Analysis of Variance).       The study reached many findings, most importantly the abstract role of the marketing innovation with its various dimensions in achieving a competitive advantage for the Cable Industry  Foundation- Generale Cable Branch- Biskra .And that is at the significance level (0,05 = α), which indicates the value of (R) that the strong relationship between the two variables "marketing innovation" and "competitive advantage" reached (0.553), while the  variable of marketing innovation interpreted (30.6%) of the variation in the level of achieving the institution’s competitive advantage under study, and depending on the value of  determination coefficient (R2). Keywords :  Marketing Innovation, Competitive Advantage, Cable Industry Foundation, Biskra. الملخص :          هدفت هذه الدراسة إلى التعرف على الدور الذي يلعبه الابتكار التسويقي بأبعاده المختلفة (ابتكار المنتوج، الابتكار الترويجي، الابتكار التوزيعي، الابتكار السعري) في تحقيق ميزة تنافسية للمؤسسات الاقتصادية الوطنية وبالتركيز على حالة مؤسسة صناعة الكوابل.          ولتحقيق أهداف الدراسة قمنا بتصميم استبانة وتوزيعها على مجتمع الدراسة، أما لتحليل البيانات فإننا اعتمدنا على برنامج SPSS. V19 ، حيث تم استخدام الأساليب الإحصائية الوصفية لمعرفة تصورات أفراد العينة لمستوى الابتكار التسويقي، ومستوى تحقيق الميزة التنافسية بالمؤسسة محل الدراسة. ولاختبار فرضيات الدراسة فقد استخدم تحليل الانحدار المتعدد (Multiple Regression Analysis)، وتحليل التباين للانحدار (Analysis of Variance).      توصلت الدراسة إلى عدة نتائج أهمها وجود دور معنوي للإبتكار التسويقي بأبعاده المختلة  في تحقيق ميزة تنافسية لمؤسسة صناعة الكوابل- فرع جنرال كابل- بسكرة وذلك عند مستوى الدلالة (0,05=α)، حيث تشير قيمة (R ) إلى أن قوة العلاقة بين المتغيرين "الابتكار التسويقي" و "الميزة التنافسية" بلغت (0.553)، فيما فسر متغير الابتكار التسويقي (%30.6) من التباين في مستوى تحقيق الميزة التنافسية للمؤسسة محل الدراسة، وذلك بالاعتماد على قيمة معامل التحديد (R 2 ) . الكلمات المفتاحية: الابتكار التسويقي، الميزة التنافسية، مؤسسة صناعة الكوابل، بسكرة.